Role of extractives on the weathering of tropical and temperate wood species in two above-ground fields: coastal or terrestrial - Ermeydan, Mahmut A.; Dizman, Riza; Tomak, Eylem D.; Can, Ahmet (Taylor & Francis Inc, 2024)
The effect of heartwood extractives on natural weathering of 5 temperate (juniper, walnut, oak, pseudoacacia, and chestnut) and 9 tropical (wenge, teak, iroko, dahoma, moabi, okan, padauk, ipe, and tatajuba) wood species against abiotic degrading agents at two sites was investigated. Wood species were exposed to three-stage extraction, then extracted and un-extracted samples were exposed outdoors for 12 months in two above-ground test sites, coastal or terrestrial. Samples were evaluated regarding moisture content, color change, surface roughness, and surface chemistry (ATR-FTIR) at 1, 3, 6, and 12 months of exposure. Results indicate that roughness and color change increased as the exposure time increased. Among the temperate species, the least rough surfaces were found in juniper, while iroko, ipe, and wenge were for tropical species. The location did not statistically affect roughness. Temperate species generally showed rougher surfaces than tropical species. The remarkable color change occurred in the first 3 months in temperate wood species and between 3 and 6 months in extractive-rich tropical wood species. The highest color change was seen in samples extracted and exposed on the terrestrial test site, while the lowest was in un-extracted samples exposed on the coast. Padauk had the most color change, while moabi had the least. The surfaces of temperate species showed darkening while the surfaces of tropical species showed lightening during the weathering exposure. FTIR studies confirmed that the change in the surface chemistry of temperate species mostly occurs in the first month, while surface degradation of some tropical species can take up to 3 months.
Keywords: Photodegradation; color change; extractives; roughness; abiotic factors; coastal & terrestrial